The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/00914037.2015.1030658
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response of Limbal Stem Cells on PHBV/Gelatin Nanofibrous Scaffold for Ocular Epithelial Regeneration

Abstract: The aim of this study was to develop a blend of nanofibrous poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)=gelatin substrate for limbal stem cell (LSC) expansion that can serve as a potential alternative substrate to replace human amniotic membrane. The human Limbus stem cell was used to evaluate the biocompatibility of substrates (nanofibrous scaffold, and human amniotic membrane) based on their phenotypic profile, viability, proliferation, and attachment ability. Biocompatibility results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Because, the structural and physical properties of electrospun nanofibres resemble those of ECM, electrospun nanofibers of synthetic or regenerated natural polymers promote cell proliferation, enhance nutrition and enable waste transfer. Thus, 3D electrospun nanofibres scaffolds have been widely used as scaffolds for various tissue engineering applications [27][28][29][30][31][32][33]. One work demonstrated that nonwoven silk nanofibrous nets were able to support the adhesion, proliferation and cell-cell interactions of variable human cell lines including osteoblasts, fibroblasts, keratinocytes and endothelial cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Because, the structural and physical properties of electrospun nanofibres resemble those of ECM, electrospun nanofibers of synthetic or regenerated natural polymers promote cell proliferation, enhance nutrition and enable waste transfer. Thus, 3D electrospun nanofibres scaffolds have been widely used as scaffolds for various tissue engineering applications [27][28][29][30][31][32][33]. One work demonstrated that nonwoven silk nanofibrous nets were able to support the adhesion, proliferation and cell-cell interactions of variable human cell lines including osteoblasts, fibroblasts, keratinocytes and endothelial cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Most common clinical substrate for ocular surface repair is human amniotic membrane owing to its biocompatibility, anti‐inflammatory efficacy, and angiogenesis ability 137. However, it also has several disadvantages, such as poor mechanical strength, semitransparent appearance, difficulty of handling, and the potential risk of disease transmission, and therefore, alternative choices should be further explored. Compared to bulk material, electrospun patches with micro/nanosize fiber dimensions and high surface area were considered advantageous in topical application or treating the anterior segment eye diseases.…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
“…It can produce the ultra fine fibers with special orientation, high surface-to-volume ratio, surface morphology, pore geometry, and three-dimensional architecture. [6][7][8][9][10][11][12][13][14][15][16][17][18] Thus, the choice of electrospinning technique takes into account the properties of the selected biomaterial, for instance, utilization of natural ECM proteins, to achieve a well-designed nanofiber scaffold, which imitates the desired natural ECM. It is obvious that collagen (CO) is the main abundant ECM protein, and it provides flexibility and structural strength to the ECM tissues.…”
Section: Introductionmentioning
confidence: 99%